Insights, current status and future perspective of JAK inhibitors in the treatment of alopecia areata - Xingqi ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Alopecia areata (AA) is a chronic heterogeneous inflammatory disease, with unknown pathogenesis. Although there are quite a few options to choose for treatment of AA, there is no specific therapic method, and neither is one therapic method for all patients. In addition, few patients with chronic course and severe type respond poorly to routine treatment. Therefore, we have urgent need for new and effective treatment. From 2014 to now, JAK inhibitors has been shown satisfactory effect on patients with AA internationally. The mechanism of JAK inhibitors in AA management is mainly through inhibiting production of cytokines by immune cells and acting to follicular epithelial cells towards anagen. According to those data from published papers and those from our study, the efficacy rate of JAK inhibitors is up to 70%~80%, especially for severe AA patients or patients with poor responder to steroid treatment. Due to high cost and potential possibility of infection, it is only used as a second line treatment. Both mechanism of action and treatment from published papers have been reviewed in this paper, as well as the insights of this new medication.